Poor Sleep Quality Associated With Enlarged Perivascular Spaces in Patients With Lacunar Stroke - Yang, Shuna; Yin, Jiangmei; Qin, Wei; Yang, Lei; Hu, Wenli (Frontiers in Neurology, 2022)
Background and Objective Enlarged perivascular spaces (EPVSs) are considered as an MRI marker of cerebral small vessel diseases and were reported to be associated with brain waste clearance dysfunction. A previous study found that interstitial fluid clearance in the mouse brain occurred mainly during sleep. However, the relationship between sleep quality and EPVS in humans has not been well-understood. Thus, we aimed to investigate the relationship between sleep and EPVS in humans. Methods This retrospective study was conducted in patients with lacunar stroke in the Neurology Department of Beijing Chaoyang Hospital. Patients with EPVS >10 on one side of the basal ganglia (BG) and white matter slice containing the maximum amount were defined as the BG-EPVS group and the white matter (WM)-EPVS group, respectively. Patients with EPVS <10 in the slice containing the maximum amount were defined as the control group. Sleep quality was evaluated by the Pittsburgh Sleep Quality Index (PSQI) including seven components, where a score of 6 or higher indicated poor sleep quality. Spearman's correlation analysis and the binary logistic regression analysis were performed to analyze the relationship between poor sleep quality and BG-EPVS and WM-EPVS, respectively. Results A total of 398 patients were enrolled in this study, including 114 patients in the BG-EPVS group and 85 patients in the WM-EPVS group. The proportion of poor sleep quality in the BG-EPVS group was higher than that in the control group (58.8 vs. 32.5%, p < 0.001). The score of PSQI, subjective sleep quality, sleep latency, sleep duration, and sleep efficiency were higher in the BG-EPVS group than that in the control group (p < 0.05). The proportion of poor sleep quality was also higher in the WM-EPVS group than that in the control group (50.6 vs. 35.3%, p = 0.031). The score of sleep duration and sleep disturbances was higher in the WM-EPVS group than that in the control group. Spearman's correlation analysis showed that poor sleep quality was positively associated with BG-EPVS (ρ = 0.264, p < 0.001) and WM-EPVS (ρ = 0.154, p = 0.044). The binary logistic regression analysis showed that poor sleep quality, longer sleep latency, and less sleep duration were independently related to BG-EPVS and poor sleep quality, less sleep duration, and more serious sleep disturbances were independently related to WM-EPVS after adjusting for confounders (P < 0.05). Conclusion Poor sleep quality was independently associated with EPVS in BG and WM.